PERHITUNGAN PREMI ASURANSI PERTANIAN BERDASARKAN INDEKS IKLIM CURAH HUJAN DENGAN MENGGUNAKAN METODE BLACK-SCHOLES DI PROVINSI LAMPUNG - Vikarti, Maulida Magdalena; Lestari, Fuji (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
Agriculture plays an important role in national economic development, but has the highest risk of loss due to its dependence on climatic conditions. One of the efforts to reduce the risk of crop failure is through an agricultural insurance program. The agricultural insurance used in this study is rainfall climate index-based agricultural insurance. This study aims to analyze the value of the rainfall climate index to be used and analyze the calculation of agricultural insurance premiums based on the rainfall climate index. The method used to determine the rainfall climate index is the Historical Burn Analysis method and the method used to calculate agricultural insurance premiums is the Black-Scholes method. The results showed variations in trigger and exit values at each BMKG station, with North Lampung Geophysical Station having the highest trigger and exit of 36,87 mm and 49,64 mm, while the highest premium was recorded at Panjang Maritime Meteorological Station at Rp 3.025.887,38. This is due to the risk of extreme events below the trigger value occurring more frequently